Monitoring training load in soccer: the ROMEI model - Montini, M.; Rocchi, J. E. (The Journal of Strength and Conditioning Research, 2022)
For a training organization, monitoring training load (TL) is of paramount importance. Despite this, a conclusive response on such topic is yet to be reported. The aims of this study were to investigate the relationship between TL indicators and to propose a new method for monitoring TL response and physical fitness. Twenty professional soccer players were retrospectively evaluated. The first phase of data analysis included 34 in-season training sessions. Subsequently, three microcycles (T1-T2-T3) of pre-season training were processed. A regression model was used to examine the relationships between internal TL (session rating of perceived exertion [s-RPE]) and external TL (energy expenditure, EE). The standard error of the regression equation was used to propose a new model called "ROMEI" (Relation of Ongoing Monitored Exercise in Individual). The level of statistical significance was set at p < 0.05. During the competitive season and the pre-season training camp, the average TL values were 65.8 ± 22 and 58.2 ± 22 minutes; 336 ± 204 and 228 ± 101 AU of s-RPE; and 29 ± 13 and 25 ± 9 kJ kJ-1 of EE, respectively. In the competitive season, the collective and average individual correlation coefficients between s-RPE and EE were r = 0.888 and r = 0.892 ± 0.05, respectively. Considering slope values (m) of the regression line, data highlighted a significant increase of +34.4 ± 15.9% in T2 vs. T3 (p < 0.001) and +38.2 ± 15.2% in T1 vs. T3 (p < 0.001). Data shown in this investigation support the use of an individualized analysis to better understand the TL administered to soccer players rather than a collective analysis. This may be accomplished with the proposed ROMEI model.